Back bay blues - Colt, Peter, 1973- (Colt, Peter, 1973- Andy Roark mystery., 2020)
"1985, Boston. In Vietnam, Andy Roark witnessed death and horrifying destruction. But for the soldiers who made it back alive, there are other casualties of war--the loss of tenderness, trust, and connection. Still feeling adrift and unsettled, Andy has struck up a welcome friendship with Nguyen, a Vietnamese restaurant owner. Sipping beer and trading memories after the restaurant shutters, Andy gradually learns of the extraordinary lengths Nguyen took to flee Saigon shortly after its fall. Andy's latest case, too, has ties to Vietnam. His new client, a beautiful and enigmatic young Vietnamese woman, hires him to investigate her uncle's murder. Andy discovers a connection to a group of refugees determined to overthrow the communist government. Led by the sinister Colonel Tran, the Committee is extorting local business owners to raise funds. The search for more answers takes Andy from Boston to Washington D.C. to San Francisco, and deep into a web of political and personal betrayal. Somewhere near the heart of this mystery is a connection to Nguyen's daring escape from Saigon. Decades may have passed, but sometimes the price of freedom twists allies into enemies, loyalties into betrayals, and truth into a web of lies . . ."--FantasticFiction.com.